Anatomical variations of the atlas arches: prevalence assessment, systematic review and proposition for an updated classification system - Baena-Caldas, Gloria P.; Mier-García, Juan F.; Griswold, Dylan P.; Herrera-Rubio, Adriana M.; Peckham, Ximara (Frontiers in Neuroscience, 2024)
Objective and Background: This study focuses on the atlas, a pivotal component of the craniovertebral junction, bridging the cranium and spinal column. Notably, variations in its arches are documented globally, necessitating a thorough assessment and categorization due to their significant implications in clinical, diagnostic, functional, and therapeutic contexts. The primary objective is to ascertain the frequency of these anatomical deviations in the atlas arches among a Colombian cohort using Cone-Beam Computed Tomography (CBCT).Methodology: Employing a descriptive, cross-sectional approach, this research scrutinizes the structural intricacies of the atlas arches in CBCT scans. Analytical parameters included sex distribution and the nature of anatomical deviations as per Currarino's classification. Statistical analyses were conducted to identify significant differences, including descriptive statistics and Chisquare tests. A systematic review of the literature was conducted in order to enhance the current Currarino's classification.Results: The study examined 839 CBCT images, with a nearly equal sex distribution (49.7% female, 50.3% male). Anatomical variations were identified in 26 instances (3%), displaying a higher incidence in females (X2[(1, N= 839) =4.0933, p=0.0430]). The most prevalent variation was Type A (2.5%), followed by Type B (0.4%), and Type G (0.2%) without documenting any other variation. The systematic review yielded 7 studies. A novel classification system for these variations is proposed, considering global prevalence data in the cervical region.The study highlights a statistically significant predominance of Type A variations in the female subset. Given the critical nature of the craniovertebral junction and supporting evidence, it recommends an amendment to Currarino's classification to better reflect these clinical observations. A thorough study of anatomical variations of the upper cervical spine is relevant as they can impact important functional aspects such as mobility as well as stability. Considering the intricate anatomy of this area and the pivotal function of the atlas, accurately categorizing the variations of its arches is crucial for clinical practice. This classification aids in diagnosis, surgical planning, preventing iatrogenic incidents, and designing rehabilitation strategies.